Mulheres Tech: Flipped Classroom for the Digital Inclusion of Domestic Workers in Brazilian Cities (Journal of Advanced Research in Social Sciences, 2025)
The Mulheres Tech project longs to promote digital inclusion and socio-emotional development among domestic workers in five Brazilian cities, addressing a group often excluded from technological advancements. With a focus on reducing inequalities, the project targets approximately 200 domestic workers who lack digital literacy skills. The methodology applied is an adapted version of the flipped classroom approach, where university students from five higher education institutions deliver basic digital literacy lessons under the supervision of professors. The language used during the classes are clear and value-neutral, avoiding biased; The project not only aims to equip domestic workers with essential digital skills for greater autonomy and better access to employment opportunities, but also to foster a sense of social responsibility among the students who taught the classes to the workers. Results demonstrate that 87.4% of domestic workers were very satisfied participating with the initiative, which highlights the effectiveness of empowering a marginalized demographic and contributing to their professional and personal development. The project demonstrates how academic collaboration can play an important role in bridging digital divides and fostering social inclusion.